Personnel selection - SACKETT, Paul R. (Institutional Knowledge at Singapore Management University, 2008)
We review developments in personnel selection since the previous review by Hough & Oswald (2000) in the Annual Review of Psycholog. We organize the review around a taxonomic structure of possible bases for improved selection, which includes (a) better understanding of the criterion domain and criterion measurement, (b) improved measurement of existing predictor methods or constructs, (c) identification and measurement of new predictor methods or constructs, (d) improved identification of features that moderate or mediate predictor-criterion relationships, (e) clearer understanding of the relationship between predictors or between predictors and criteria (e.g., via meta-analytic synthesis), (f) identification and prediction of new outcome variables, (g) improved ability to determine how well we predict the outcomes of interest, (b) improved understanding of subgroup differences, fairness, bias, and the legal defensibility, (i) improved administrative ease with which selection systems can be used, (j) improved insight into applicant reactions, and (k) improved decision-maker acceptance of selection systems.